NORMALIZATION OF STRESS-STRAIN CURVES FROM CRS CONSOLIDATION TEST AND ITS APPLICATION TO CONSOLIDATION ANALYSIS - K. Suzuki; K. Yasuhara (International Association of Lowland Technology, 2005)
The results of Constant Rate of Strain (CRS) consolidation test carried out at 0.02 %/min are normalized in order to produce stress-strain curves corresponding to strain rates slower than 0.02%/min. The normalizing procedure consists of two steps: 1) define the curve corresponding to OCR=1, and 2) normalize the difference between the curves defined in the first step and that directly obtained from CRS test. The resulting stress-strain curves are applied to the consolidation analysis of a marine clay deposit loaded by a test embankment. The comparison between the observed field behavior and the consolidation analysis presented here suggests that the normalizing procedure demonstrated the usefulness of CRS consolidation test in consolidation analysis.